From Design to Performance: 3-D Printing-Enabled Optimization of Low-Cost Droplet Microfluidics - Anshori, Isa; Sarwono, Febricetta Zahraketzia; Fa’iq, Muhammad Azhar; Putra, Narendra Kurnia; Suwardy, Joko; Purwidyantri, Agnes; Prabowo, Briliant Adhi (IEEE sensors journal, 2024)
Droplet microfluidic is a novel technique for screening applications that offers benefits such as high throughput, low sample consumption, and improved single-cell analysis capabilities. This technique involves creating and manipulating small droplets of fluid that can serve as discrete reactors for various assays and experiments. However, droplet-based microfluidics have a complex, relatively high-cost, and time-consuming process. In this research, a T-shaped junction droplet generator is fabricated using 3-D printing. By using 3-D printing, droplet generator fabrication becomes simple, fast, and low-cost. The fabricated droplet-based microfluidics are then evaluated for their performance. Through several optimizations in dimension and flow rate, a droplet generator with a channel height of 0.5 mm and a width of 1 mm was successfully fabricated using the 3-D printing method. The droplet generator can produce monodisperse droplets with optimum performance with identical flow rates of [Formula Omitted] and [Formula Omitted] around 2.5 mL/h. The experimental result also in a good agreement with a 2-D numerical result based on computational fluid dynamics (CFDs) simulation.